Hypericum boyacense (Hypericaceae), a new broad-leaved species of the Eastern Cordillera of Colombia, with a key to identify the species of the group - González, Favio (Phytotaxa, 2025)
Hypericum boyacense is described as new species from the Eastern Cordillera of Colombia. The species, morphologically related to H. cymobrathys, grows in subpáramo vegetation of the Natural Reserve Ranchería, municipality of Paipa, Department of Boyacá. The new species stands as a distinct species mainly by a combination of unique vegetative and reproductive characters, especially the herbaceous habit, the leaves and sepals strongly veined and with densely muricate surface due to the presence of dark glands, the pair of leaves immediately below the terminal flower reduced to lineariform bracts, the flowers 8–12 mm in diameter at full anthesis, and with broadly obovate petals with 13 or 15 longitudinal veins. The species is known only from the type specimen.